The Effectiveness of Dark Chocolate Consumption on Dysmenorrhea in Adolescent Girls at SMK Widya Nusantara (Office Management in Business Institutions): Efektivitas Konsumsi Dark Chocolate Terhadap Dismenorea Pada Remaja Putri SMK Widya Nusantara (Manajemen Perkantoran Lembaga Bisnis) - Dea Okta Viantri; Simanjuntak, Farida Mentalina; Lumban Siantar, Rupdi (Jurnal Ilmiah Kesehatan, 2025)
Background : Dysmenorrhea is menstrual pain where this condition causes pain in the lower abdomen. Dysmenorrhea is caused by uterine contractions. Condition It often causes pain irregularly and feels strong that can interfere with daily activities. According to Riskesdas, in 2018 the prevalence of dysmenorrhea reached 107,673 people (64.25%), consisting of primary dysmenorrhea reaching 59,671 people (54.89%) and 9,496 people (9.36%) who experienced secondary dysmenorrhea.(Kemenkes RI, 2018). Treatment of dysmenorrhea can be done by non-pharmacological complementary therapy, one of which is by consumption dark chocolate. Methods : To determine the Effectiveness of Dark Chocolate Consumption on Dysmenorrhea in Adolescent Girls of SMK Widya Nusantara. Purpose : To determine the effectiveness of dates on hemoglobin levels in pregnant women with anemia at Puskesmas Karang Mulya Kabupaten Bekasi 2024. Method: Using a quasi-experimental research design with a pre-test and post-test two-group design. The sample in this study amounted to 30 respondents. 15 respondents who consumed dark chocolate and 15 control respondents. The sampling technique uses purposive sampling. The research instrument used a numeric rating scale sheet. Result: Based on the results of the wilcoxon test in the intervention group, a probability value (P value) of 0.002 (p < 0.05) was obtained. In the control group, a probability value (P value) of 1,000 (p >0.05) was obtained. Conclusion : There is an Effectiveness of Dark Chocolate Consumption on Reducing Dysmenorrhea in Adolescents of SMK Widya Nusantara Keywords : Adolescent Women, Dysmenorrhea, Dark Chocolate